Inappropriate use of psychotropic drugs in older individuals: implications for practice. (June 2013) - Azermai, Majda; Bourgeois, Jolyce; Somers, Annemie; Petrovic, Mirko
Frailty at old age and institutionalization in nursing homes are often associated with multiple chronic diseases (multimorbidity) requiring multiple medications (polypharmacy). Among these chronic conditions, mental health problems (e.g., dementia, depression and insomnia) are common. Psychotropic drugs are frequently used as a treatment approach for these conditions, and the prevalence of their use is high among community-dwelling older adults, but even higher in nursing homes. Furthermore, within the problem of polypharmacy and inappropriate prescribing, psychotropic drugs (defined in this article as antipsychotics, benzodiazepines and antidepressants) constitute a significant proportion. The use of psychotropics in older adults remains controversial given the risk of adverse effects, in contrast to the limited effectiveness. Guidelines advise a thorough risk–benefit analysis before the initiation of psychotropics, in addition to time-limited use and discontinuation. In the future, serious efforts should be undertaken to tackle the burden of inappropriate psychotropic prescribing in older adults by incorporating a multidisciplinary approach and by offering credible alternatives.